Primary ciliary dyskinesia in an infant with post-infectious bronchiolitis obliterans and failure to thrive: A case report - Shekhar, S Shubhranshu; De, Sanjukta (Indian Journal of Case Reports, 2025)
We report the case of a 9-month-old male infant with recurrent severe viral pneumonia, culminating in bronchiolitis obliterans and chronic respiratory morbidity. The clinical course was marked by multiple pediatric intensive care unit admissions, prolonged oxygen dependency, and recurrent bacterial superinfections. High-resolution computed tomography revealed bronchiectasis and fibrotic changes. Given the chronicity of symptoms, a clinical suspicion of Primary Ciliary Dyskinesia (PCD) was raised. Genetic analysis detected heterozygous variants of uncertain significance in the DNAH1 and LRRC6 genes. This case highlights the diagnostic and management complexities in infants with post-viral chronic lung disease and the importance of early consideration and evaluation for underlying genetic etiology, such as PCD.